A descriptive study of the role of maternal behavior in the survival of Markhor (Capra falconeri) kids - Asif, Daniel (SLU/Dept. of Animal Environment and Health (until 231231), 2019)
In a herd of captive Markhors, observations were made to investigate the elements of maternal behavior, interactions of mothers with their kids, visitor’s effect and welfare. Females isolated themselves from other conspecifics before parturition and selected a parturition site in the elevated part of the enclosure. After birth, the kids concealed themselves under a rock formation for at least eight days and their mothers visited them in their hiding for nursing. Each doe allowed only her own kid to suckle, after identifying the kid. When the hiding phase was over the mothers communicated with their kids by bleats. A close maternal-offspring bond was observed between does and their kids. Nursing time was significantly longer in the elevated rocky part of the enclosure (48.5 ±2.3 sec, 49 ± 1.4 sec) compared to the lower part (17.8 ±1.8 sec, 18.1 ± 1.3 sec). The higher number of nursing events were recorded in the evening or late afternoon and least suckling events were recorded during the late morning, noon and early afternoon. The number of bleats by the does were significantly more in the lower part of the enclosure (median 6/day) compared to the elevated rocky part (median 1.5/day). Babysitting behavior was observed among two mothers. Despite the display of babysitting behavior, allonursing behavior as well as the kid-stealing/adoption behavior was absent. The mothers were vigilant when they were accompanied by the kids. The kids spent relatively more time uphill than downhill with an increasing number of visitors. Moreover, the kids spent significantly more time in the elevated part of the enclosure (146.2 ± 63.9 mins) compared to the flat lower part (73.7 ± 32 mins) (P < 0.05, Paired t-test t = 4.30 P = 0.016) for each category of the visitors. The results of this study suggest that the Markhor individuals perceived the elevated part safer than the lower part of their enclosure. Keeping Markhors in captivity for the purpose of conservation, provision of an enclosure which mimics their natural habitat would not only provide them optimum welfare but also facilitates their successful reproduction.